Permitting as a Bottleneck in Swedish Housing Projects - Azar, Kaihan; Krasniqi, Burim (My University, 2026)
Housing delivery remains a major challenge in Swedish cities and growth regions, where demand for new housing is high. One reason is that many housing projects face long lead times before construction can begin. These delays are often connected to planning and permitting, where projects must pass through formal stages and balance legal, technical, political, and public interests. The aim of this study was to examine major permitting related issues in Swedish housing projects and to understand how these issues are addressed in practice. The study also examined whether these issues are similar across housing projects or vary depending on project type. The research was based on a qualitative approach, combining a literature review with eight semi-structured interviews with actors involved in housing development, municipal planning, research, and housing policy. The findings show that permitting-related delays are not caused by one actor or one step. Instead, they are created through the combined effect of legal requirements, municipal responsibilities, actor coordination, technical investigations, political decisions, public participation, appeals, limited resources, and project-specific conditions. Detailed development planning appears as a central bottleneck, especially when risks are identified late or when requirements and responsibilities are unclear. The study shows that permitting issues are mainly addressed through earlier preparation, risk identification, stronger coordination, parallel work, public dialogue, digital support, clearer prioritization, and dedicated capacity. These measures do not remove the need for legal review, public participation, or formal approval. Rather, they help actors work earlier and more systematically within the existing system. The findings also show that permitting issues vary between project types. Infill projects are often exposed to local objections and political sensitivity, while large urban projects often face coordination challenges. Projects requiring a new or amended detailed development plan are generally more uncertain than projects that fit within existing planning conditions. The main conclusion is that permitting delays should be understood as a system issue rather than a single-actor problem. Reducing unnecessary delays therefore requires better coordination and earlier risk handling, while still protecting legal certainty, democracy, and public interests.
Keywords: Swedish housing projects, permitting, planning process, lead times, detailed development plan, coordination and project delays